Attempts to retreat from a dead-ended long capillary by backward swimming in Paramecium - Kunita, Itsuki; Kuroda, Shigeru; Ohki, Kaito; Nakagaki, Toshiyuki (Frontiers in Microbiology, 2014)
We have observed how the ciliate Paramecium attempts to retreat from the dead-end of a long capillary that is too narrow for turning. After many trial-and-error episodes of short-term backward swimming (SBS), which is the conventional avoidance behavior exhibited in free swimming when an obstacle is faced, long-term backward swimming (LBS) that lasted five to ten times longer was developed. LBS may have a beneficial effect for complete withdrawal from the capillary space, although in our experiment it was impossible for the organism to do so due to the capillary length. In order to identify a physically possible mechanism for LBS, we propose model equations for the membrane potential of Hodgkin-Huxley type, which describe the control of ciliary movement. The physiological implications and physical mechanism of the development of LBS are discussed.